UTILIZATION OF TOMATOES (SOLANUM LYCOPERSICUM L.) TO REDUCE THE RISK OF PROSTATE CANCER: A SYSTEMATIC REVIEW - P, Ardhiana; R, Atika; Y, Riska; Proverawati, Atikah (International Journal of Biomedical Nursing Review, 2022)
Introduction: Prostate cancer is cancer that develops in the prostate gland of the male reproductive system. It is caused by prostate cells that begin to mutate and multiply out of control. Prostate cancer is the most common cancer in men globally after lung cancer. Lycopene has been identified as an antioxidant substance that is potentially an anticancer substance. Lycopersicum is a carotenoid most commonly found in tomatoes (Solanum lycopersicum L.). However, some studies’ results for the relationship between lycopene in tomatoes (Solanum lycopersicum L.) with the risk of prostate cancer still show inconsistencies. Purpose: This study aims to find out and update the data related to the correlation between lycopene content in tomatoes and the risk of prostate cancer. Methods: This research method uses a systematic review method by searching research journals from PubMed, Google Scholar, and Science Direct database with inclusion criteria for analysis. Results: As a result, 6 out of 5 similar research journals for analyses related to the correlation between lycopene in tomatoes (Solanum lycopersicum L.) with a reduced risk of prostate cancer. Discussion: Prostate cancer patients have a low antioxidant content in their blood, thus increasing the stress of oxidation and lipid peroxidation. Reducing the risk of oxidation requires an intake of antioxidant substances that function as an anticancer substances, one of which is lycopene in tomatoes (Solanum lycopersicum L.). Lycopene serves as a free radical carcinogenesis substance and increases overall antioxidants, thereby reducing oxidative damage to lipids, proteins, and DNA. Although there are still inconsistencies in some studies related to the co-relationship of the two, this study concludes that there is a tendency to a correlation between lycopene in tomatoes (Solanum lycopersicum L.) with drop risk of prostate cancer. Conclusion: Thus, effective levels of lycopene in tomatoes (Solanum lycopersicum L.), which should be consumed at a certain time to lower the risk of prostate cancer are still unclear in number and more research is still needed related to this.